2004
DOI: 10.1111/j.1366-9516.2004.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting rapid invasion of the Florida Everglades by Old World Climbing Fern (Lygodium microphyllum)

Abstract: Lygodium microphyllum (Cav.) R. Br. (Lygodiaceae) is a climbing fern that is becoming one of the worst non‐indigenous invasive plant species in the greater Everglades ecosystem of southern Florida, USA. We examined the fern across a range of scales including the seasonality of its spore production, its height growth within infested sites and its community ecology. These attributes, combined with a series of aerial transects that identified L. microphyllum infestations across southern Florida, were used to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 26 publications
0
64
1
Order By: Relevance
“…Managing L. microphyllum has been a significant challenge for land resource managers and researchers due to its extensive rapid invasion in natural areas of south Florida. Once established, L. microphyllum dominates both understory and overstory native wetland habitats, and has the ability to grow in varying hydrological (Gandiaga et al 2009), nutrient (Volin et al 2010), soil pH (Soti et al 2014, and light gradients (Volin et al 2004). Soti et al (2014) have shown that L. microphyllum is highly dependent on mycorrhizal fungi for growth and phosphorus uptake which could highly enhance its invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Managing L. microphyllum has been a significant challenge for land resource managers and researchers due to its extensive rapid invasion in natural areas of south Florida. Once established, L. microphyllum dominates both understory and overstory native wetland habitats, and has the ability to grow in varying hydrological (Gandiaga et al 2009), nutrient (Volin et al 2010), soil pH (Soti et al 2014, and light gradients (Volin et al 2004). Soti et al (2014) have shown that L. microphyllum is highly dependent on mycorrhizal fungi for growth and phosphorus uptake which could highly enhance its invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Two-thirds of southern Florida is susceptible to invasion by this weed (Volin et al, 2004). The pyralid moth Neomusotima conspurcatalis and the gall mite Floracarus perrepae have been introduced and become established (Boughton and Pemberton, 2009;Boughton and Pemberton, unpublished data).…”
Section: Other Invaders Damaging To Wetlandsmentioning
confidence: 99%
“…The rhizome grows at, or just below, the soil surface and, once established, can withstand temporary inundation and variable water levels (Gandiaga et al 2009, Mueller 1982a, Volin et al 2004. Leaves form dorsally on the rhizome, follow a single rank, and develop from a single cell produced by the apical meristem (Mueller 1982a).…”
Section: Fern Biologymentioning
confidence: 99%
“…Subdivisions of pinnules (pinnulules) are usually unlobed if sterile but fertile pinnulules will form sorophores of enrolled leaf margins (Gandolfo et al 2000) that bear sporangia on the abaxial surface. A typical pinnulule may produce more than 28,000 spores, which are wind-dispersed and can be produced throughout the year (Volin 2004). Lygodium microphyllum spores are achlorophyllous and are reported to maintain their viability for four years (Stocker et al 2008).…”
Section: Fern Biologymentioning
confidence: 99%